EVALUASI KESESUAIAN LAHAN UNTUK PENGEMBANGAN HUTAN RAKYAT DI DESA BERABAN KABUPATEN PARIGI MOUTONG - Hamka, Hamka (JSTT, 2015)
The study aimed to determine both of actual and potential land suitability classes for teak, mahogany and sengon as well as to identify the potential of land availability for the private forest development in Beraban village. The study was conducted in November 2014 - January 2015. It applied the matching system between land use or growing plant requirements and land quality/characteristics of a given area. Land suitability classes are determined by physical properties (land characteristics /quality) major limitation in assessing land suitability classes. The results showed actual land suitability classes of teak were marginal suitability (S3), and not suitable (N1); mahogany was considered as moderate suitability (S2), marginal suitability (S3), and not suitable (N1); while sengon was assessed considered as moderate suitability (S2), marginal suitability (S3), and not suitable (N1).Â